Conceptualizing the effective mechanisms of a social needs case management program shown to reduce hospital use: a qualitative study - Mark D. Fleming; Nadia Safaeinili; Margae Knox; Elizabeth Hernandez; Emily E. Esteban; Urmimala Sarkar; Amanda L. Brewster (BMC, 2022)
Abstract Background Social needs case management programs are a strategy to coordinate social and medical care for high-risk patients. Despite widespread interest in social needs case management, not all interventions have shown effectiveness. A lack of evidence about the mechanisms through which these complex interventions benefit patients inhibits effective translation to new settings. The CommunityConnect social needs case management program in Contra Costa County, California recently demonstrated an ability to reduce inpatient hospital admissions by 11% in a randomized study. We sought to characterize the mechanisms through which the Community Connect social needs case management program was effective in helping patients access needed medical and social services and avoid hospitalization. An in-depth understanding of how this intervention worked can support effective replication elsewhere. Methods Using a case study design, we conducted semi-structured, qualitative interviews with case managers (n = 30) and patients enrolled in social needs case management (n = 31), along with field observations of patient visits (n = 31). Two researchers coded all interview transcripts and observation fieldnotes. Analysis focused on program elements identified by patients and staff as important to effectiveness. Results Our analyses uncovered three primary mechanisms through which case management impacted patient access to needed medical and social services: [1] Psychosocial work, defined as interpersonal and emotional support provided through the case manager-patient relationship, [2] System mediation work to navigate systems, coordinate resources, and communicate information and [3] Addressing social needs, or working to directly mitigate the impact of social conditions on patient health. Conclusions These findings highlight that the system mediation tasks which are the focus of many social needs assistance interventions offered by health care systems may be necessary but insufficient. Psychosocial support and direct assistance with social needs, enabled by a relationship-focused program, may also be necessary for effectiveness.